A first scoring approach for evaluating the European Ocean Observing Community - Abed El Rahman Hassoun; Toste Tanhua; Emma Heslop; Inga Lips; Marta Álvarez; George Petihakis; Maribel I. García-Ibáñez; Dimitris Velaoras; Michele Giani; Hermann W. Bange; Christian Lønborg; Johannes Karstensen (Frontiers in Marine Science, 2024)
The European Ocean Observing Community (EOOC) integrates inputs from diverse entities dedicated to comprehensively monitoring and forecasting oceanic phenomena in European Seas. With increasing climate and anthropogenic pressures, the urgency of ensuring the EOOC’s preparedness to observe Essential Ocean Variables (EOVs) is evident. This paper advocates for the adoption of a scoring approach designed to evaluate the readiness of the EOOC in observing and forecasting key ocean phenomena. The proposed scoring methodology can be applied at both European and potentially regional and/or national levels, and emerges as a transformative tool for scrutinizing the EOOC’s capability to predict and monitor key ocean phenomena. Our findings, based on the application of the scoring approach, suggest that while the community demonstrates commendable readiness levels for certain oceanic phenomena, 83% remain in developing stages, oscillating between “Idea” and “Trial” readiness levels. A closer examination exposes critical shortages predominantly in the coordination and observational facets (Process), and data management and information products (Output). The implications of these identified gaps reach far beyond academic realms, profoundly affecting diverse sectors and societal resilience (e.g., energy sector). The suggested scoring approach serves as a clear call for strategic investments and heightened support for the European observing community. By adopting a regular and systematic scoring methodology, we not only measure progress at present but also pave the way for a resilient and future-ready EOOC.

Towards a sustained and fit-for-purpose European ocean observing and forecasting system - Toste Tanhua; Pierre-Yves Le Traon; Nicole Köstner; Dina Eparkhina; Gabriel Navarro; Martha Bonnet Dunbar; Sabrina Speich; Ananda Pascual; Karina von Schuckmann; Giovanni Liguori; Johannes Karstensen; Abed El Rahman Hassoun; et al. (Frontiers in Marine Science, 2024)
The EU funded project EuroSea brought together key actors of the European ocean observing and forecasting communities with key users of the ocean observing products and services in order to better integrate existing ocean observation systems and tools, and to improve the delivery of ocean information to users. EuroSea was constructed around the ocean observing value chain that connects observations to users of ocean information, and, just as intended, the value chain concept was a useful prism to improve the system. In this article, we summarize some of the main take-home messages from EuroSea on the needs for developing the European Ocean Observing System and its links with modeling and forecasting systems. During the project, the challenges and gaps in the design and coordination of the European ocean observing and forecasting system were identified and mapped. Many gaps and challenges related to the observations of physical, chemical and biological Essential Ocean Variables were identified. Some of these gaps are related to technological developments, while others are caused by insufficient and short-term funding leading to a not sustainable system, management, and cooperation between different entities, as well as limitations in foresight activities, policies and decisions. This article represents a compilation of the broader needs for advancing the observing and forecasting system, and is meant as a guide for the community, and to funders and investors to advance ocean observing and the delivery of ocean information in Europe. To enhance the sustainability of ocean observations, which is paramount for a reliable provision of quality oceanographic data and services, several recommendations were compiled for ocean observing networks, frameworks, initiatives, as well as the ocean observing funders within the European nations, and the European Commission.

The European Ocean Observing Community: urgent gaps and recommendations to implement during the UN Ocean Decade - Abed El Rahman Hassoun; Toste Tanhua; Inga Lips; Emma Heslop; George Petihakis; Johannes Karstensen (Frontiers in Marine Science, 2024)
The interdisciplinary community of ocean and coastal observers and modelers in Europe is driven by national observing needs for prediction and management of intricate processes shaping Europe’s Seas. Not all observing needs can be addressed by nations alone and various coordination activities exist to overcome fragmentation and create cross benefit within the European Ocean Observing Community (EOOC). This way critical insights into impacts of climate change on European Waters and cross border marine resources management can be achieved. Based on a large number of published material, this article is identifying and addressing the current state of activities of the EOOC and states gaps that potentially prevent efficacy. Key challenges include spatial and temporal coverage in observations, data integration, accessibility, uncertainties in projections, technological hurdles, and engagement and communication gaps. Detailed recommendations are provided for identified gaps, offering valuable insights for stakeholders, funders, and supporters of the EOOC. These recommendations, extending beyond academic interest, carry significant implications for climate change mitigation, marine resource management efficiency, ecosystem resilience, disaster preparedness, economic benefits, and the broader scientific advancements in European marine science, thereby benefiting society at large. As the world undergoes transformative changes impacting all facets of European life, substantial investment and support for the EOOC are crucial for precise information, accurate predictions, supporting sustained services that contribute to business growth and community resilience, and a sustainable ocean.

Uncertainty and Consistency Assessment in Multiple Microplastic Observation Datasets in the Baltic Sea - Jun She; Natalja Buhhalko; Kati Lind; Arun Mishra; Villu Kikas; Elisa Costa; Chiara Gambardella; Alessio Montarsolo; Marco Faimali; Francesca Garaventa; Inga Lips (Frontiers in Marine Science, 2022)
This paper aims to quantify data uncertainties in marine microplastic measurements, including spatiotemporal sampling error and sample volume estimation error, identify impacts of varying mesh sizes, sampling and analysis methods, and evaluate consistency in multiple microplastic observation datasets. Twenty-seven datasets on surface marine microplastics with particle size >100 µm in the Baltic Sea are compiled. Results show that the trawl datasets have a spatiotemporal sampling error of 25% for microlitter concentration, 36% for microplastic fiber concentrations and 40-56% for microplastic particle concentration. By taking surface currents and wave-induced Stokes drift into account, the sample volume of the trawl measurements is corrected, leading to a mean microplastic concentration correction of 12%. The differences of microplastic concentration between datasets with varying mesh sizes from 100 – 500 µm are not statistically significant. Analysis methods, however, can lead to significant differences in microplastic datasets. The dataset consistency is further examined among the three dataset categories using trawl, pump and bulk sampling techniques. It is found that an individual dataset is often self-consistent. Most of the datasets within one monitoring category are more consistent than those from different categories. More than 70% of the datasets within individual categories are consistent, which have mean microplastic concentration significantly smaller than the rest of the datasets. Significant inconsistencies are identified between different data categories. Six out of eight highest relative standard deviations are found in the pump and bulk datasets. The median value of the mean microplastic concentration from the 10 pump datasets is about 4.5 times as much as that of the 14 trawl datasets, both for fiber and non-fiber particles. Significant differences are also identified on microplastic fiber fraction in different dataset categories. Two thirds of the 13 bulk and pump datasets have a microplastic fiber fraction >85% while the 14 trawl datasets show much lower microplastic fiber fractions between 45-70%. In addition, the particle collection efficiency, potential leakage of particles with irregular shapes, clogging, the false zero samples and related lower limit of the detectable microplastic concentration for given sampling methods and water environment, are also discussed.

Spatiotemporal Variability of Microplastics in the Eastern Baltic Sea - Arun Mishra; Natalja Buhhalko; Kati Lind; Inga Lips; Taavi Liblik; Germo Väli; Urmas Lips (Frontiers in Marine Science, 2022)
Microplastic (MP) pollution is present in all aquatic environments and is gaining critical concern. We have conducted sea surface MP monitoring with a Manta trawl at 16 sampling stations in the eastern Baltic Sea in 2016–2020. The concentrations varied from 0.01 to 2.45 counts/m 3 (0.002–0.43 counts/m 2 ), and the mean was 0.49 counts/m 3 (0.08 counts/m 2 ). The fibers and fragments had, on average, an approximately equal share in the samples. Correlation between the concentration of fibers and fragments was higher near the land and weaker further offshore. The following spatial patterns were revealed: higher mean values were detected in the Baltic Proper (0.65 counts/m 3 ) (0.11 counts/m 2 ) and the Gulf of Finland (0.46–0.65) (0.08–0.11) and lower values were detected in the Gulf of Riga (0.33) (0.06) and Väinameri Archipelago Sea (0.11) (0.02). The difference between the latter three sub-basins and the meridional gradient in the Gulf of Riga can likely be explained by the degree of human pressure in the catchment areas. The MP concentration was higher in autumn than in summer in all regions and stations, probably due to the seasonality of the biofouling and consequent sinking rate of particles. A weak negative correlation between the wind speed and the MP concentration was detected only in the central Gulf of Finland, and positive correlation in the shallow area near river mouth. We observed a 60-fold difference in MP concentrations during coastal downwelling/upwelling. Divergence/convergence driven by the (sub)mesoscale processes should be one of the subjects in future studies to enhance the knowledge on the MP pathways in the Baltic Sea.

Developing benthic monitoring programmes to support precise and representative status assessments: a case study from the Baltic Sea - Henrik Nygård; Mats Lindegarth; Alexander Darr; Grete E. Dinesen; Ole R. Eigaard; Inga Lips (Environmental Monitoring and Assessment, 2020)
Benthic habitats and communities are key components of the marine ecosystem. Securing their functioning is a central aim in marine environmental management, where monitoring data provide the base for assessing the state of marine ecosystems. In the Baltic Sea, a > 50-year-long tradition of zoobenthic monitoring exists. However, the monitoring programmes were designed prior to the current policies, primarily to detect long-term trends at basin-scale and are thus not optimal to fulfil recent requirements such as area-based periodic status assessments. Here, we review the current monitoring programmes and assess the precision and representativity of the monitoring data in status assessments to identify routes for improvement. At present, the monitoring is focused on soft-bottoms, not accounting for all habitat types occurring in the Baltic Sea. Evaluating the sources of variance in the assessment data revealed that the component accounting for variability among stations forms the largest proportion of the uncertainty. Furthermore, it is shown that the precision of the status estimates can be improved, with the current number of samples. Reducing sampling effort per station, but sampling more stations, is the best option to improve precision in status assessments. Furthermore, by allocating the sampling stations more evenly in the sub-basins, a better representativity of the area can be achieved. However, emphasis on securing the long-term data series is needed if changes to the monitoring programmes are planned.

The winter stratification phenomenon and its consequences in the Gulf of Finland, Baltic Sea - Taavi Liblik; Germo Väli; Inga Lips; Madis-Jaak Lilover; Villu Kikas; Jaan Laanemets (Ocean Science, 2020)
Stratification plays an essential role in the marine ecosystem, with a shallow mixed layer being one of the preconditions for enhanced primary production in the ocean. In the Baltic Sea, the general understanding is that the upper mixed layer (UML) is well below the euphotic zone in winter. In this study, we demonstrate that wintertime shallow stratification is common in the Gulf of Finland and it forms at a depth comparable to the euphotic zone in January–February. The onset of restratification is likely associated with the annual cycle of westerly winds, which ease off in late January–early February. Stratification is first invoked along the northern coast by the westward advection of riverine water forced by easterly winds and is expanded to the south when the prevailing wind direction changes from an easterly to a westerly direction. Haline stratification emerges approximately 1 month later in the southern part of the gulf. Winter restratification can occur in the entire gulf and also in the absence of ice; thus, it is a regular seasonal feature in the area. Interannual variations in the wintertime UML correspond with variations in the North Atlantic Oscillation. Chlorophyll a concentrations in winter can be comparable to mid-summer; the limiting factor for phytoplankton bloom in winter is likely insufficient solar radiation.

The Importance of Mesodinium rubrum at Post-Spring Bloom Nutrient and Phytoplankton Dynamics in the Vertically Stratified Baltic Sea - Inga Lips; Urmas Lips (Frontiers in Marine Science, 2017)

Competitive advantage and higher fitness in native populations of genetically structured planktonic diatoms - Sirje Sildever; Josefin Sefbom; Inga Lips; Anna Godhe (Environmental Microbiology, 2016)
Summary It has been shown that the planktonic diatom Skeletonema from neighbouring areas are genetically differentiated despite absence of physical dispersal barriers. We revisited two sites, Mariager Fjord and Kattegat, NE Atlantic, and isolated new strains. Microsatellite genotyping and F‐statistics revealed that the populations were genetically differentiated. An experiment was designed to investigate if populations are locally adapted and have a native competitive advantage. Ten strains from each location were grown individually in native and foreign water to investigate differences in produced biomass. Additionally, we mixed six pairs, one strain from each site, and let them grow together in native and foreign water. Strains from Mariager Fjord and Kattegat produced higher biomass in native water. In the competition experiment, strains from both sites displayed higher relative abundance and demonstrated competitive advantage in their native water. The cause of the differentiated growth is unknown, but could possibly be attributed to differences in silica concentration or viruses in the two water types. Our data show that dispersal potential does not influence the genetic structure of the populations. We conclude that genetic adaptation has not been overruled by gene flow, but instead the responses to different selection conditions are enforcing the observed genetic structure.

Dark nutrient uptake at low temperature and subsequent light use efficiency by the dinoflagellate Heterocapsa triquetra - Karin Ojamäe; Anneliis Peterson; Inga Lips (Marine Biology Research, 2016)

Physical barriers and environmental gradients cause spatial and temporal genetic differentiation of an extensive algal bloom - Anna Godhe; Conny Sjöqvist; Sirje Sildever; Josefin Sefbom; Sara Harðardóttir; Mireia Bertos‐Fortis; Carina Bunse; Susanna Gross; Emma Johansson; Per R. Jonsson; Saghar Khandan; Catherine Legrand; et al. (Journal of Biogeography, 2016)
Aim To test if a phytoplankton bloom is panmictic, or whether geographical and environmental factors cause spatial and temporal genetic structure. Location Baltic Sea. Method During four cruises, we isolated clonal strains of the diatom Skeletonema marinoi from 9 to 10 stations along a 1132 km transect and analysed the genetic structure using eight microsatellites. Using F ‐statistics and Bayesian clustering analysis we determined if samples were significantly differentiated. A seascape approach was applied to examine correlations between gene flow and oceanographic connectivity, and combined partial Mantel test and RDA based variation partitioning to investigate associations with environmental gradients. Results The bloom was initiated during the second half of March in the southern and the northern‐ parts of the transect, and later propagated offshore. By mid‐April the bloom declined in the south, whereas high phytoplankton biomass was recorded northward. We found two significantly differentiated populations along the transect. Genotypes were significantly isolated by distance and by the south–north salinity gradient, which illustrated that the effects of distance and environment were confounded. The gene flow among the sampled stations was significantly correlated with oceanographic connectivity. The depletion of silica during the progression of the bloom was related to a temporal population genetic shift. Main conclusions A phytoplankton bloom may propagate as a continuous cascade and yet be genetically structured over both spatial and temporal scales. The Baltic Sea spring bloom displayed strong spatial structure driven by oceanographic connectivity and geographical distance, which was enhanced by the pronounced salinity gradient. Temporal transition of conditions important for growth may induce genetic shifts and different phenotypic strategies, which serve to maintain the bloom over longer periods.

Multi-sensor in situ observations to resolve the sub-mesoscale features in the stratified Gulf of Finland, Baltic Sea - Urmas Lips; Villu Kikas; Taavi Liblik; Inga Lips (Ocean Science, 2016)
High-resolution numerical modeling, remote sensing, and in situ data have revealed significant role of sub-mesoscale features in shaping the distribution pattern of tracers in the ocean's upper layer. However, in situ measurements are difficult to conduct with the required resolution and coverage in time and space to resolve the sub-mesoscale, especially in such relatively shallow basins as the Gulf of Finland, where the typical baroclinic Rossby radius is 2–5 km. To map the multi-scale spatiotemporal variability in the gulf, we initiated continuous measurements with autonomous devices, including a moored profiler and Ferrybox system, which were complemented by dedicated research-vessel-based surveys. The analysis of collected high-resolution data in the summers of 2009–2012 revealed pronounced variability at the sub-mesoscale in the presence of mesoscale upwelling/downwelling, fronts, and eddies. The horizontal wavenumber spectra of temperature variance in the surface layer had slopes close to −2 between the lateral scales from 10 to 0.5 km. Similar tendency towards the −2 slopes of horizontal wavenumber spectra of temperature variance was found in the seasonal thermocline between the lateral scales from 10 to 1 km. It suggests that the ageostrophic sub-mesoscale processes could contribute considerably to the energy cascade in such a stratified sea basin. We showed that the intrusions of water with different salinity, which indicate the occurrence of a layered flow structure, could appear in the process of upwelling/downwelling development and relaxation in response to variable wind forcing. We suggest that the sub-mesoscale processes play a major role in feeding surface blooms in the conditions of coupled coastal upwelling and downwelling events in the Gulf of Finland.

Vertical dynamics of summer phytoplankton in a stratified estuary (Gulf of Finland, Baltic Sea) - Urmas Lips; Inga Lips; Taavi Liblik; Villu Kikas; Kristi Altoja; Natalja Buhhalko; Nelli Rünk (Ocean Dynamics, 2011)

The influence of a coastal upwelling event on chlorophyll a and nutrient dynamics in the surface layer of the Gulf of Finland, Baltic Sea - Natalja Kuvaldina; Inga Lips; Urmas Lips; Taavi Liblik (Hydrobiologia, 2010)

Potential phytoplankton indicator species for monitoring Baltic coastal waters in the summer period - Andres Jaanus; Kaire Toming; Seija Hällfors; Kaire Kaljurand; Inga Lips (Hydrobiologia, 2009)

Identification of the coastal zone of the central and eastern Gulf of Finland by numerical modeling, measurements, and remote sensing of chlorophyll a - Gennadi Lessin; Viktoria Ossipova; Inga Lips; Urmas Raudsepp (Hydrobiologia, 2009)

Abiotic factors influencing cyanobacterial bloom development in the Gulf of Finland (Baltic Sea) - Inga Lips; Urmas Lips (Hydrobiologia, 2008)

Distribution Patterns of Isomorphic Cold-Water Dinoflagellates (Scrippsiella/Woloszynskia Complex) Causing ‘red tides’ in the Baltic Sea - Andres Jaanus; Susanna Hajdu; Seppo Kaitala; Agneta Andersson; Kaire Kaljurand; Iveta Ledaine; Inga Lips; Irina Olenina (Hydrobiologia, 2006)